2017
DOI: 10.1039/c7sm01224a
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant effects on droplet dynamics and deposition patterns: a lattice gas model

Abstract: A coarse-grained lattice gas model is developed to study pattern forming processes in drying drops containing surfactant. By performing Monte Carlo simulations of the model, the coupled dynamics of surfactant and liquid evaporation and the resulting oscillatory dynamics at the contact line are elucidated. We show that the coupled drop dynamics and the resulting final deposition patterns can be altered by adsorption kinetics. For slow adsorption rates, surfactant molecules recirculate along with colloidal parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…The difficulties mainly exist in two aspects. The first one is the modeling of droplet evaporation, considering the wide range of length and time scales, variation of contact angle, contact line retreating, evaporative cooling, substrate heating, and surfactant contamination, and so forth. Capillary and Marangoni flow can be induced by the evaporation of the droplet, which has been widely applied in the numerical model to affect particle transportation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulties mainly exist in two aspects. The first one is the modeling of droplet evaporation, considering the wide range of length and time scales, variation of contact angle, contact line retreating, evaporative cooling, substrate heating, and surfactant contamination, and so forth. Capillary and Marangoni flow can be induced by the evaporation of the droplet, which has been widely applied in the numerical model to affect particle transportation.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1998, the modeling community keeps working to expand our understanding of particle moving mechanisms. Previous numerical studies mainly focus on particle transportation inside the bulk fluid, while some recent progress has been made to reveal the particle accumulation behavior along the liquid–air interface. ,,, Other focuses are the surfactant contamination at the surface and particle attraction by capillary force . The effect of particle transportation behavior on droplet evaporation has also been explored, including the influence of adsorbed particles on surface tension, evaporation flux, and self-pinning induced by particle accumulation .…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common phenomena related to the droplets is evaporation, that is, vaporization, which plays an essential role in various industrial fields. For example, the droplet evaporation has been classified into uniform, coffee-ring, and multi-ring patterns [1][2][3][4][5][6][7][8][9][10] for various uses, including ink-jet printing techniques [11][12][13] and fuel evaporation in a combustion engine [14][15][16][17]. Some researchers have also found applications for droplet evaporation in nano-chromatography [18,19], medical diagnosis, food quality assessment, and medicine manufacture [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…A series of work has been done since then, aiming for small contact angle (up to 40°). Due to the convenience of this analytical solution in describing the droplet evaporation and the flow field induced, it has been widely applied in many modeling works to describe the particle transportation behavior and to simulate the deposition patterns [111][112][113][114].…”
Section: Evaporation Induced Inner Flowsmentioning
confidence: 99%
“…The study done by Deegan et al [95] has shown that an outward flow could be induced by the evaporation of droplet with a pinned boundary, leading to the deposits at contact line. As a result, the original KMC model has been modified to incorporate the convection of nanoparticles [113,138]. Jung et al [139] have proposed another form of Hamiltonian equation:…”
Section: Kinetic Monte Carlo Modelmentioning
confidence: 99%